Responsiveness and the influence to public trust: the study on local government service delivery / Nor Zaini Zainal Abidin, Kuppusamy Singaravelloo and Intan Syahriza Azizan - Zainal Abidin, Nor Zaini; Singaravelloo, Kuppusamy; Azizan, Intan Syahriza (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Responsiveness is a principle of administrative accountability towards clients and customers. Indeed, local government service delivery is the main component in the government that exemplifies responsiveness function that connects the public and local authorities. Being the service provider to the public at their localities, fast response is an important ingredient to ensure public confidence and trust which simultaneously leads to work quality. Thus, responsiveness of local government affects the positive communion between these two stakeholders. This paper focuses on the influence of responsiveness towards public trust especially on local government service delivery in Selangor and Kuala Lumpur. These two local authorities were chosen to conform whether they are “listening bureaucrats” which are sensitive and sympathetic to public outcry. This research found that there was a strong connection between responsiveness and public trust. Moreover, the findings confirm that speed on any queries and request of service by local government paying the heed in influencing public to trust local government and government in power. Thus, the result showed that responsiveness is important be it for the state or federal government, because responsiveness can gain public to trust the government.